Chapter Massimo il Greco e il pensiero politico di Dante nella Russia del Cinquecento - Garzaniti, Marcello (Biblioteca di Studi di Filologia Moderna, 2022)
Maximus the Greek (c. 1470-1555/1556), one of the most influential members of the Greek diaspora in Russia, arrived in Moscow from Constantinople with an official delegation (1518) and remained there until his death at the time of Ivan the Terrible. It was only in the second half of the last century that it was discovered Maximus the Greek must be identified with Michael Trivolis, a young Greek humanist educated in Florence at the end of the 15th century. Like many of his contemporaries, Trivolis had been influenced by the preaching of Girolamo Savonarola. Systematic research on the relation between the work of Savonarola and the humanists close to him and the writings of Maximus the Greek has not yet been conducted, but the data collected to date allow us to establish a close relationship within the context of certain religious, philosophical, and social themes. The examination of a text dedicated to the exercise of power by emperors and princes, the Discourse more extended, written by Maximus the Greek by the time of Ivan the Terrible, shows not only direct correlations with some of Savonarola's cantos, but also the presence of images and themes from Dante Alighieri's Divine Comedy and Cristoforo Landino's Comento, starting with the idea of empire. The collections of Maximus the Greek's writings, in which this Discourse appears, were widely disseminated, and left a deep mark on Russian culture.